Molecular determinants of substrate specificity revealed by the structure of Clostridium thermocellum arabinofuranosidase 43A from glycosyl hydrolase family 43 subfamily 16. Issue 12 (5th December 2016) - Goyal, Arun; Ahmed, Shadab; Sharma, Kedar; Gupta, Vikas; Bule, Pedro; Alves, Victor D.; Fontes, Carlos M. G. A.; Najmudin, Shabir
Abstract : The structure of C. thermocellum arabinofuranosidase 43A reveals how the enzyme acts specifically in the removal of arabinose side chains from arabinoxylan but not from pectic arabinan. Abstract : The recent division of the large glycoside hydrolase family 43 (GH43) into subfamilies offers a renewed opportunity to develop structure–function studies aimed at clarifying the molecular determinants of substrate specificity in carbohydrate‐degrading enzymes. α‐l ‐Arabinofuranosidases (EC 3.2.1.55) remove arabinose side chains from heteropolysaccharides such as xylan and arabinan. However, there is some evidence suggesting that arabinofuranosidases are substrate‐specific, being unable to display a debranching activity on different polysaccharides. Here, the structure of Clostridium thermocellum arabinofuranosidase 43A ( Ct Abf43A), which has been shown to act in the removal of arabinose side chains from arabinoxylan but not from pectic arabinan, is reported. Ct Abf43A belongs to GH43 subfamily 16, the members of which have a restricted capacity to attack xylans. The crystal structure of Ct Abf43A comprises a five‐bladed β‐propeller fold typical of GH43 enzymes. Ct Abf43A displays a highly compact architecture compatible with its high thermostability. Analysis of Ct Abf43A along with the other member of GH43 subfamily 16 with known structure, the Bacillus subtilis arabinofuranosidase BsAXH‐m2, 3, suggests that the specificity of subfamily 16 for arabinoxylan is conferred by a long surface substrate‐binding cleft that is complementary to the xylan backbone. The lack of a curved‐shaped carbohydrate‐interacting platform precludes GH43 subfamily 16 enzymes from interacting with the nonlinear arabinan scaffold and therefore from deconstructing this polysaccharide.